Quality of Life After Partial or Whole-Breast Irradiation in Breast-Conserving Therapy for Low-Risk Breast Cancer: 1-Year Results of a Phase 2 Randomized Controlled Trial - Song, Yu-Chun; Sun, Guang-Yi; Fang, Hui; Tang, Yu; Song, Yong-Wen; Hu, Chen; Qi, Shu-Nan; Chen, Bo; Jing, Hao; Tang, Yuan; Jin, Jing; Liu, Yue-Ping; et al. (Frontiers in Oncology, 2021)
Purpose: To report patients’ quality of life (QoL) at 1 year in a phase 2 randomized trial comparing partial breast irradiation (PBI) with whole-breast irradiation (WBI) after breast-conserving surgery (BCS) for breast cancer. Methods: Women aged  45 years with low-risk breast cancer after BCS were randomly assigned (1:1) to receive PBI (40 Gy in 10 fractions over 2 weeks) or WBI (43.5 Gy in 15 fractions over 3 weeks). The primary endpoint—the incidence of toxicities of grade 2 or higher—will be reported when participants complete 5 years of follow-up. QoL was assessed at baseline (T0), at the end of radiotherapy (RT) (T1), 6 months (T2) and 1 year (T3) after RT by using the EORTC QLQ-C30 and QLQ-BR23 questionnaires. We calculated the scores for all QOL subscales and differences in mean scores were compared. This study was registered at ClinicalTrials.gov (NCT03583619). Results: Between June 2017 and January 2019, 140 women were randomly assigned to receive PBI or WBI (n = 70 per group). Fifty-nine and 56 patients treated with PBI and WBI, respectively, were eligible for the QoL analysis. There were no significant differences in any subscale scores at T0, T1, T2, or T3 between the PBI and WBI arms. The scores for most QoL subscales that were influenced by RT recovered to a similar or better level relative to T0 scores within 1 year after RT, except for the scores of the dyspnea subscale. Longitudinal analysis showed that time since RT had a significant impact on physical functioning, role functioning, social functioning, fatigue, pain, dyspnea, financial difficulties, body image, and breast and arm symptoms. Conclusion: PBI using the intensity-modulated RT affords QoL comparable to that provided by WBI. Most QoL subscale scores that were influenced by RT recovered to a similar or better level relative to baseline scores within 1 year after RT.